Uso do Processo de Avaliação Mútua aliado a Conceitos de Gamificação como suporte ao Estudo Colaborativo em Ambientes de EaD - Nascimento, Anielton José do (2016)
One of the main problems of the Distance Learning (DL) is the lack in communication and collaboration among students, which is mainly caused by the physical distance among them. Researches in education show that collaboration between students, where they assist each other in understanding the educational content, is one of the fundamental parts of the learning process. Virtual learning environments, such as Moodle, provide some resources such as Forums and Chats to support collaboration. However, such resources are not enough to motivate collaboration. This and other aspects are the main causes to the high number of retention and dropout of students in the DL courses, since they are not able to adapt themselves to the features of this type of learning modality. Our work uses concepts of mutual evaluation, integrated to gamification elements, as an alternative to motivate collaboration among students in small groups. In order, the literature indicates that collaborative processes are more efficient when applied to groups composed of 4 or 5 students. One of the main contributions of our work is to develop an automatic mutual evaluation process, which can be integrated to the mutual evaluation carried out by students, so that the final results are more reliable. The validation of this proposal was carried out with disciplines of the Informatics Graduation course of the Virtual UFPB. The results show that, apart to increase the reliability, our approach also enables the identification of biases along the mutual evaluation process and generates different ways to compare the performance of students and groups of students, considering different attributes proposed in this work.